YOLO-Pika: a lightweight improved model of YOLOv8n incorporating Fusion_Block and multi-scale fusion FPN and its application in the precise detection of plateau pikas - Liu, Yihao; Zhao, Jianyun; Xu, Changjun; Hou, Yuedi; Jiang, Yuxiang (Frontiers in Plant Science, 2025)
The plateau pika (Ochotona curzoniae) is a keystone species on the Qinghai–Tibet Plateau, and its population density—typically inferred from burrow counts—requires rapid, low-cost monitoring. We propose YOLO-Pika, a lightweight detector built on YOLOv8n that integrates (1) a Fusion_Block into the backbone, leveraging high-dimensional mapping and fine-grained gating to enhance feature representation with negligible computational overhead, and (2) an MS_Fusion_FPN composed of multiple MSEI modules for multi-scale frequency-domain fusion and edge enhancement. On a plateau pika burrow dataset, YOLO-Pika increases mAP50 by 3.4 points and mAP50–95 by 5.0 points while reducing parameters by 22.7% and FLOPs by 0.01%; AP improves for small, medium, and large targets. On a public Brandt’s vole hole dataset, it achieves a further 4.9-point gain in mAP50 and reduces false detections from localization errors, redundancy, and background noise by 30–50%. Compared with five state-of-the-art lightweight detectors (including YOLOv10), YOLO-Pika attains the highest detection accuracy with the fewest parameters. These results show that YOLO-Pika balances real-time performance, detection precision, and deployment feasibility, offering a practical, scalable solution for rodent burrow detection and alpine grassland damage assessment with strong cross-regional generalization.